الديناميك الجزيئي والانتقال الطوري - شيماء, رابحي; نبيلة, زيدان (universty of elouedجامعة الوادي, 2020)
"الديناميك الجزيئي هي طريقة محاكاة حاسوبية تعتمد على طريقة ميكانيكية لدراسة الأنظمة متعددة الجسيمات، فهي بهذا تحاكي ديناميك هذه الأنظمة بإستخدام معادلات الحركة المجهرية الضرورية لتقدير القوة بين كل جسيمين. يتطلب حساب هذه القوة معرفة كمون التفاعل الذي يعطى بكمون ليونارد جونس. تتضمن المحاكاة بالديناميك الجزيئي حل معادلات الحركة لكل جسيم في النظام باستخدام خوارزمية فرلات. في هذه المذكرة تم التطرق إلى شرح هذه الطريقة ومبدأ عملها وأهم الشروط الواجب تحققها من أجل محاكاة دقيقة. أُنجزت محاكاة الديناميك الجزيئي لوصف تصرف غاز الأرغون عن طريق دراسة حركة ذراته لمشاهدة وصوله إلى التوازن الحراري. تمت أيضا محاكاة ظاهرة الانصهار بنفس الطريقة انطلاقا من حالة صلبة مناسبة وصولا إلى الحالة السائلة المنشودة. الفكرة المهمة التي تم عرضها هي إمكانية حساب كميات ماكروسوبية إنطلاقا من قوانين كلاسيكية على المستوى المجهري.""Molecular dynamics is a computer simulation method based on a mechanical approach for studying multiparticle systems. It, therefore, simulates the dynamics of these systems using the microscopic equations of motion that need to estimate the force between any two particles. Calculation of the force requires knowledge of the interaction potential given by a Lennard-Jones potential. A molecular-dynamics simulation consists of solving the equations of motion for every particle in the system using Verlet algorithm. In this dissertation, the explanation of this method, its principle of work and the most important conditions that must be fulfilled for an accurate simulation have been covered. A molecular dynamics simulations is performed to describe the behavior of Argon gas by studying the motion of its atoms in order to see how it reaches a thermal equilibrium. The melting phenomenon was also simulated in the same way, starting from a suitable solid state until the desired liquid state is established. The most important idea shown in this work is the capability of calculating macroscopic quantities using classical laws of motion at a microscopic level."
مذكرة تخرج ماستر فيزياء
Keywords: محاكاة الديناميك الجزيئي، الانتقال الطوري، كمون ليونارد جونس، خوارزمية فرلات، الانصهار، توزيع ماكسويل.; Molecular dynamics simulation, Phase transition, Lennard Jones ptential, Verlet algorithm, Melting, Maxwell distribution.